BTK, NUTM2A, and PRPF19 Are Novel KMT2A Partner Genes in Childhood Acute Leukemia - Elena Zerkalenkova; Svetlana Lebedeva; Aleksandra Borkovskaia; Olga Soldatkina; Olga Plekhanova; Grigory Tsaur; Michael Maschan; Aleksey Maschan; Galina Novichkova; Yulia Olshanskaya (Biomedicines, 2021)
Chromosomal rearrangements of the human KMT2A/MLL gene are associated with acute leukemias, especially in infants. KMT2A is rearranged with a big variety of partner genes and in multiple breakpoint locations. Detection of all types of KMT2A rearrangements is an essential part of acute leukemia initial diagnostics and follow-up, as it has a strong impact on the patients’ outcome. Due to their high heterogeneity, KMT2A rearrangements are most effectively uncovered by next-generation sequencing (NGS), which, however, requires a thorough prescreening by cytogenetics. Here, we aimed to characterize uncommon KMT2A rearrangements in childhood acute leukemia by conventional karyotyping, FISH, and targeted NGS on both DNA and RNA level with subsequent validation. As a result of this comprehensive approach, three novel KMT2A rearrangements were discovered: ins(X;11)(q26;q13q25)/KMT2A-BTK, t(10;11)(q22;q23.3)/KMT2A-NUTM2A, and inv(11)(q12.2q23.3)/KMT2A-PRPF19. These novel KMT2A-chimeric genes expand our knowledge of the mechanisms of KMT2A-associated leukemogenesis and allow tracing the dynamics of minimal residual disease in the given patients.